Titanium alloy containing coating and preparation method thereof
By printing the AlMgScZr coating on the surface of the titanium alloy, the problems of low hardness of the titanium alloy and easy coating fall off are solved, and the metallurgical combination of the coating and the substrate are improved at high temperatures.
Patent Information
- Application Number
- CN202510522636.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2025-07-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Titanium alloy has low hardness, prone to adhesion wear and wear of abrasive particles, poor resistance at high temperatures, easy coating to fall off and poor overall performance.
The AlMgScZr coating was printed on the surface of the titanium alloy by laser selection melting method. The specific parameters were laser power 365-375W, scanning speed 950-1050mm/s, powder thickness 0.02-0.04mm, scanning spacing 0.01-0.02mm, spot diameter 0.1-0.15mm, and the coating consists of Al:Mg:Sc:Zr powder, with a mass ratio of 93-95:4-6:0.1-0.4:0.1-0.4, and particle diameter 15-40μm.
The surface hardness and wear resistance of titanium alloy are improved, the coating is metallurgically combined with the matrix, and is not easy to fall off, there are no obvious pores and through-type cracks inside, which enhances the interface bonding strength.
Smart Images

Figure SMS_1 
Figure HDA0005374421050000011 
Figure HDA0005374421050000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of coated titanium alloys, and particularly relates to a coated titanium alloy and a preparation method thereof. Background Art
[0002] Titanium alloy materials have excellent properties. They have good comprehensive mechanical properties, strong corrosion resistance, and can be used as the main lightweight structural materials. They are often used to manufacture aircraft landing gears, engines, compressors and other types of casings. Although titanium alloys have many advantages, there are also many disadvantages that limit their scope of use. Titanium alloys have low hardness and are prone to adhesive wear, abrasive wear and other phenomena. Based on the performance characteristics of titanium and titanium alloys with poor resistance at high temperatures, in order for titanium alloys to be heated at higher temperatures without being oxidized and damaged, it is necessary to carry out protective treatment on titanium alloys to improve the high-temperature potential and comprehensive performance of titanium alloys. Moreover, the coating is formed during the cooling process due to the large difference in the thermal expansion coefficients of the matrix and the coating composition phases, and also because the thermal conductivity of titanium alloys is poor, resulting in a large temperature gradient from the outside to the inside during the cooling process. The formation of directional solidification from the surface to the inside is the main reason for the crack to propagate along the grain boundaries. Therefore, the research on the surface treatment of titanium alloys has important significance. Summary of the Invention
[0003] In view of the above deficiencies in the prior art, the present invention provides a coated titanium alloy and a preparation method thereof. The coated titanium alloy has good hardness, wear resistance and high-temperature oxidation resistance. The titanium alloy and the coating have good bonding strength, the coating is not easy to fall off, the coating has excellent performance, and there are no obvious pores and through cracks inside, effectively solving the problems of easy coating peeling and poor comprehensive performance in the prior art.
[0004] To achieve the above object, the technical solution adopted by the present invention to solve its technical problems is:
[0005] A preparation method of a coated titanium alloy, comprising the following steps:
[0006] (1) Pretreat the titanium alloy to remove surface impurities;
[0007] (2) Place the treated titanium alloy in a vacuum environment, and introduce argon as a protective gas into it. Then, use the selective laser melting method to print a coating on the surface of the titanium alloy. The selective laser melting parameters are: the laser power is 365 - 375W, the scanning speed is 950 - 1050mm / s, the powder spreading thickness is 0.02 - 0.04mm, the scanning spacing is 0.01 - 0.02mm, the spot diameter is 0.1 - 0.15mm, and a coated titanium alloy is obtained after cooling.
[0008] Further, the titanium alloy is TC4.
[0009] Further, in step (1), the pretreatment process is ultrasonic cleaning for 8 - 12 min.
[0010] Further, in step (2), the coating is made of AlMgScZr powder, and the mass ratio of Al:Mg:Sc:Zr in the powder is 93 - 95:4 - 6:0.4 - 1:0.1 - 0.4.
[0011] Further, in step (2), the particle size of the AlMgScZr powder is 15 - 40 μm.
[0012] Further, in step (2), the selective laser melting parameters are: laser power is 370 W, scanning speed is 1000 mm / s, powder layer thickness is 0.03 mm, scanning spacing is 0.01 mm, and spot diameter is 0.1 mm.
[0013] A titanium alloy with a coating is prepared by the above method.
[0014] The beneficial effects produced by the present invention are as follows:
[0015] 1. The preparation method of the present invention is simple in operation and low in production cost. The surface coating of the obtained titanium alloy is metallurgically bonded to the substrate, with good bonding strength and not easy to fall off. It not only improves the surface hardness of the alloy, but also can improve the coating structure, making there be no obvious pores and through - cracks in the coating, improving the hardness and wear resistance of the titanium alloy, and effectively solving the problems of easy coating peeling and poor comprehensive performance in the prior art.
[0016] 2. After selective laser melting on the surface of the titanium alloy, diffusion occurs between Ti in the titanium alloy and Al in the powder, forming Ti - Al intermetallic compounds. Sc in the AlMgSc powder will also form intermetallic compounds with Ti and disperse between the titanium aluminide compounds. The formed intermetallic compounds can inhibit the excessive growth of Ti - Al intermetallic compounds, thereby changing the interfacial bonding strength between the titanium alloy and the AlMgSc coating; Mg in the AlMgSc powder forms a substitutional solid solution, further improving the interfacial bonding strength; the stable metal compounds formed after selective laser melting have both the physical properties of metal materials and the characteristics of high melting point and high hardness of ceramic materials. The coating thickness is controllable, and the coating is metallurgically bonded to the substrate, having better wear resistance than the substrate.
[0017] 3. In the present invention, by selecting specific printing parameters, the mutual solubility effect between the powder and the titanium alloy can be improved, which can not only increase the bonding strength of the coating, but also avoid the formation of brittle components in the coating, improving the comprehensive performance of the coating. Description of the Drawings
[0018] Figure 1 It is the microstructural diagram of the material in Example 1;
[0019] Figure 2 EDS analysis diagram of the material in Example 1;
[0020] Figure 3 Microstructure diagram of the material in Comparative Example 1;
[0021] Figure 4 EDS analysis diagram of the material in Comparative Example 1;
[0022] Figure 5 Microstructure diagram of the material in Comparative Example 2;
[0023] Figure 6 EDS analysis diagram of the material in Comparative Example 2;
[0024] Figure 7 Microstructure diagram of the material in Comparative Example 3;
[0025] Figure 8 EDS analysis diagram of the material in Comparative Example 3;
[0026] Figure 9 Microstructure diagram of the material in Comparative Example 4;
[0027] Figure 10 EDS analysis diagram of the material in Comparative Example 4;
[0028] Figure 11 Microstructure diagram of the material in Comparative Example 5;
[0029] Figure 12 EDS analysis diagram of the material in Comparative Example 5. Detailed implementation manners
[0030] In order to make the objectives, technical solutions and advantages of the present invention clearer and more understandable, the present invention will be further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments.
[0031] Therefore, the detailed description of the embodiments of the present invention provided below is not intended to limit the scope of the claimed present invention, but only represents the selected embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.
[0032] It should be noted that relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprising", "including" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements not only includes those elements, but also includes other elements not expressly listed, or elements inherent to such process, method, article or device. Without further limitation, an element defined by the statement "comprising an..." does not exclude the presence of additional identical elements in the process, method, article or device comprising the element.
[0033] The features and performance of the present invention will be further described in detail below in conjunction with the embodiments and the drawings.
[0034] Example 1
[0035] A titanium alloy with a coating, and its preparation method includes the following steps:
[0036] (1) Cut the titanium alloy TC4 into sheets, then polish and grind the surface of the titanium alloy, and then ultrasonically pretreat the titanium alloy for 12 min to remove surface impurities;
[0037] (2) Fix the treated titanium alloy on the substrate of the 3D printing device, then place it in a vacuum environment, and introduce argon as a protective gas into it. Then, use the selective laser melting method to print the AlMgScZr coating on the surface of the titanium alloy. The mass ratio of Al:Mg:Sc:Zr in the AlMgScZr powder is 94:5:0.7:0.3, the particle size of the AlMgScZr powder is 20 μm, and the selective laser melting parameters are: laser power is 370 W, scanning speed is 1000 mm / s, powder spreading thickness is 0.03 mm, scanning spacing is 0.01 mm, spot diameter is 0.1 mm. After cooling, a titanium alloy with a coating is obtained.
[0038] Example 2
[0039] A titanium alloy with a coating, and its preparation method includes the following steps:
[0040] (1) Cut the titanium alloy TC4 into sheets, then polish and grind the surface of the titanium alloy, and then ultrasonically pretreat the titanium alloy for 8 min to remove surface impurities;
[0041] (2) Fix the processed titanium alloy on the substrate of the 3D printing device, then place it in a vacuum environment, and introduce argon gas as the protective gas. Then, use the selective laser melting method to print an AlMgScZr coating on the surface of the titanium alloy. The mass ratio of Al:Mg:Sc:Zr in the AlMgScZr powder is 93:6:0.6:0.4, the particle size of the AlMgScZr powder is 15 μm, and the selective laser melting parameters are: laser power is 365 W, scanning speed is 950 mm / s, powder spreading thickness is 0.02 mm, scanning spacing is 0.02 mm, spot diameter is 0.15 mm. After cooling, a titanium alloy with a coating is obtained.
[0042] Example 3
[0043] A titanium alloy with a coating, and its preparation method includes the following steps:
[0044] (1) Cut the titanium alloy TC4 into sheets, then polish and grind the surface of the titanium alloy, and then perform ultrasonic pretreatment on the titanium alloy for 8 - 12 min to remove surface impurities;
[0045] (2) Fix the processed titanium alloy on the substrate of the 3D printing device, then place it in a vacuum environment, and introduce argon gas as the protective gas. Then, use the selective laser melting method to print an AlMgScZr coating on the surface of the titanium alloy. The mass ratio of Al:Mg:Sc:Zr in the AlMgScZr powder is 95:4:0.9:0.1, the particle size of the AlMgScZr powder is 40 μm, and the selective laser melting parameters are: laser power is 375 W, scanning speed is 1050 mm / s, powder spreading thickness is 0.03 mm, scanning spacing is 0.01 mm, spot diameter is 0.1 mm. After cooling, a titanium alloy with a coating is obtained.
[0046] Comparative Example 1
[0047] A titanium alloy with a coating, and its preparation method includes the following steps:
[0048] (1) Cut the titanium alloy TC4 into sheets, then polish and grind the surface of the titanium alloy, and then perform ultrasonic pretreatment on the titanium alloy for 12 min to remove surface impurities;
[0049] (2) Fix the processed titanium alloy on the substrate of the 3D printing device, then place it in a vacuum environment, and introduce argon gas as the protective gas. Then, use the selective laser melting method to print an AlMgScZr coating on the surface of the titanium alloy. The mass ratio of Al:Mg:Sc:Zr in the AlMgScZr powder is 94:5:0.7:0.3, the particle size of the AlMgScZr powder is 20 μm, and the selective laser melting parameters are: laser power is 350 W, scanning speed is 1000 mm / s, powder spreading thickness is 0.03 mm, scanning spacing is 0.01 mm, spot diameter is 0.1 mm. After cooling, a titanium alloy with a coating is obtained.
[0050] Comparative Example 2
[0051] A titanium alloy with a coating, and its preparation method includes the following steps:
[0052] (1) Cut the titanium alloy TC4 into sheets, then polish and grind the surface of the titanium alloy, and then perform ultrasonic pretreatment on the titanium alloy for 12 minutes to remove surface impurities;
[0053] (2) Fix the processed titanium alloy on the substrate of the 3D printing device, then place it in a vacuum environment, and introduce argon gas as the protective gas. Then, use the selective laser melting method to print an AlMgScZr coating on the surface of the titanium alloy. The mass ratio of Al:Mg:Sc:Zr in the AlMgScZr powder is 94:5:0.7:0.3, the particle size of the AlMgScZr powder is 20 μm, and the selective laser melting parameters are: laser power is 380 W, scanning speed is 1000 mm / s, powder spreading thickness is 0.03 mm, scanning spacing is 0.01 mm, spot diameter is 0.1 mm. After cooling, a titanium alloy with a coating is obtained.
[0054] Comparative Example 3
[0055] A titanium alloy with a coating, and its preparation method includes the following steps:
[0056] (1) Cut the titanium alloy TC4 into sheets, then polish and grind the surface of the titanium alloy, and then perform ultrasonic pretreatment on the titanium alloy for 12 minutes to remove surface impurities;
[0057] (2) Fix the processed titanium alloy on the substrate of the 3D printing device, then place it in a vacuum environment, and introduce argon gas as a protective gas. Then, use the selective laser melting method to print an AlMgScZr coating on the surface of the titanium alloy. The mass ratio of Al:Mg:Sc:Zr in the AlMgScZr powder is 90:6:3:1, the particle size of the AlMgScZr powder is 20 μm, and the selective laser melting parameters are: laser power is 370 W, scanning speed is 1000 mm / s, powder spreading thickness is 0.03 mm, scanning spacing is 0.01 mm, spot diameter is 0.1 mm. After cooling, a titanium alloy with a coating is obtained.
[0058] Comparative Example 4
[0059] A titanium alloy with a coating, and its preparation method includes the following steps:
[0060] (1) Cut the titanium alloy TC4 into sheets, then polish and grind the surface of the titanium alloy, and then perform ultrasonic pretreatment on the titanium alloy for 12 minutes to remove surface impurities;
[0061] (2) Fix the processed titanium alloy on the substrate of the 3D printing device, then place it in a vacuum environment, and introduce argon gas as a protective gas. Then, use the selective laser melting method to print an AlMgScZr coating on the surface of the titanium alloy. The mass ratio of Al:Mg:Sc:Zr in the AlMgScZr powder is 94:5:0.7:0.3, the particle size of the AlMgScZr powder is 20 μm, and the selective laser melting parameters are: laser power is 370 W, scanning speed is 800 mm / s, powder spreading thickness is 0.03 mm, scanning spacing is 0.01 mm, spot diameter is 0.1 mm. After cooling, a titanium alloy with a coating is obtained.
[0062] Comparative Example 5
[0063] A titanium alloy with a coating, and its preparation method includes the following steps:
[0064] (1) Cut the titanium alloy TC4 into sheets, then polish and grind the surface of the titanium alloy, and then perform ultrasonic pretreatment on the titanium alloy for 12 minutes to remove surface impurities;
[0065] (2) Fix the processed titanium alloy on the substrate of the 3D printing device, then place it in a vacuum environment, and introduce argon gas as the protective gas. Then, use the selective laser melting method to print the AlMgScZr coating on the surface of the titanium alloy. The mass ratio of Al:Mg:Sc:Zr in the AlMgScZr powder is 94:5:0.7:0.3, the particle size of the AlMgScZr powder is 20 μm, and the selective laser melting parameters are: laser power is 370 W, scanning speed is 1250 mm / s, powder spreading thickness is 0.03 mm, scanning spacing is 0.01 mm, spot diameter is 0.1 mm. After cooling, the titanium alloy with the coating is obtained.
[0066] Test Example
[0067] Taking the materials prepared in Example 1 and Comparative Examples 1-5 as examples, observe the microstructure of the materials and conduct EDS analysis. The specific results are shown in Tables 1-6 and Figure 1-12 .
[0068] Table 1: EDS analysis spectrum of the material in Example 1
[0069] Element Signal type Wt% At% Mg EDS 0.27 0.41 Al EDS 34.00 47.74 Ti EDS 62.69 49.59 V EDS 2.80 2.08 Mn EDS 0.25 0.17 Total amount 100.00 100.00
[0070] Table 2: EDS analysis spectrum of the material in Comparative Example 1
[0071] Element Signal type Wt% At% O EDS 2.80 4.71 Mg EDS 4.09 4.52 Al EDS 88.42 88.15 Sc EDS 0.65 0.39 Ti EDS 3.46 1.94 Mn EDS 0.58 0.28 Total amount 100.00 100.00
[0072] Table 3: EDS analysis spectrum of the material in Comparative Example 2
[0073] Element Signal type Wt% At% Al EDS 39.08 53.30 Sc EDS 0.38 0.31 Ti EDS 57.88 44.47 V EDS 2.66 1.92 Total amount 100.00 100.00
[0074] Table 4: EDS analysis spectrum of the material in Comparative Example 3
[0075] Element Signal type Wt% At% O EDS 1.72 3.13 Mg EDS 3.97 4.75 Al EDS 73.86 79.74 Sc EDS 0.44 0.28 Ti EDS 18.53 11.26 V EDS 1.00 0.57 Mn EDS 0.48 0.26 Total amount 100.00 100.00
[0076] Table 5: EDS analysis spectrum of the material in Comparative Example 4
[0077]
[0078]
[0079] Table 6: EDS analysis spectrum of the material in Comparative Example 5
[0080] Element Signal type Wt% At% O EDS 2.58 4.57 Mg EDS 3.53 4.11 Al EDS 78.44 82.24 Sc EDS 0.60 0.38 Ti EDS 13.58 8.02 V EDS 0.64 0.35 Mn EDS 0.62 0.32 Total amount 100.00 100.00
[0081] Figure 1Microstructure diagram of the material in Example 1; it can be seen that the boundary between the matrix and the coating is very straight. The structure at the coating joint is finer and more uniform than that of the matrix, and no obvious micro-gap is found. No obvious cracks or holes are found in the coating structure. The structure at the joint diffuses and connects with the matrix, achieving metallurgical bonding.
[0082] Figure 2 EDS analysis diagram of the material in Example 1; combining with the analysis spectrum in Table 1, it can be seen that the mass ratio of Ti atoms to Al atoms is close to 2:1. Under the action of high temperature, the Al element diffuses towards the matrix alloy direction, while the Ti element diffuses towards the coating direction under the action of high temperature, indicating that atomic diffusion is sufficient and it is easier to form stable intermetallic compounds.
[0083] Figure 3 Microstructure diagram of the material in Comparative Example 1; it can be seen that cracks appear in the coating, extending to the matrix in many places, the crack depth is relatively large, and there is a large area of collapse in the coating, with poor flatness, and it cannot play the due protective role for the matrix.
[0084] Figure 4 EDS diagram of the material in Comparative Example 1; combining with Table 2, it can be seen that the mass ratio of Ti atoms to Al atoms is close to 1:33. It is speculated that the lower laser power cannot provide more energy, resulting in insufficient diffusion of Al element and Ti element.
[0085] Figure 5 Microstructure diagram of the material in Comparative Example 2; it can be seen that multiple cracks appear in the whole coating, the cracks penetrate from the coating to the matrix, and most of the cracks are concentrated at the joint between the coating and the matrix, seriously affecting the coating quality.
[0086] Figure 6 EDS diagram of the material in Comparative Example 2. Combining with Table 3, it can be seen that Mg element is not detected in the coating. It is speculated that it may be due to the too high laser power, resulting in the evaporation of Mg element, thereby affecting the performance of the overall coating.
[0087] Figure 7 Microstructure diagram of the material in Comparative Example 3. It can be seen that cracks appear at the joint between the coating and the matrix, and a large number of holes appear at the joint, and the structure is not dense enough.
[0088] Figure 8 EDS diagram of the material in Comparative Example 3. Combining with Table 4, it can be seen that although the mass percentage of Ti is relatively high, its atomic percentage is relatively low, indicating that the atomic weight of titanium is large. It is speculated that this is caused by adjusting the ratio.
[0089] Figure 9 Microstructure diagram of the material in Comparative Example 4. It can be seen that a large number of cracks appear at the joint between the coating and the matrix.
[0090] Figure 10 It is the EDS diagram of the material in Comparative Example 4. Combining with Table 5, it can be seen that the carbon content in the material has increased significantly, which may be introduced due to improper operation. Cracks appear in the material, and it is speculated that they are caused by too slow scanning speed.
[0091] Figure 11 It is the microstructure diagram of the material in Comparative Example 5. It can be seen that a large number of cracks still occur at the junction of the coating and the substrate.
[0092] Figure 12 It is the EDS diagram of the material in Comparative Example 5. Combining with Table 6, it can be seen that the proportion of Al in the material has decreased, and it is speculated that it may be caused by too fast scanning speed.
Claims
1. A preparation method of a coated titanium alloy, characterized in that, It includes the following steps: (1) Pretreat the titanium alloy to remove surface impurities; (2) Place the treated titanium alloy in a vacuum environment, introduce argon gas as a protective gas, and then use the selective laser melting method to print a coating on the surface of the titanium alloy. The selective laser melting parameters are: laser power is 365 - 375 W, scanning speed is 950 - 1050 mm / s, powder layer thickness is 0.02 - 0.04 mm, scanning spacing is 0.01 - 0.02 mm, spot diameter is 0.1 - 0.15 mm. After cooling, a titanium alloy with a coating is obtained.
2. The preparation method of the coated titanium alloy according to claim 1, characterized in that, The titanium alloy is TC4.
3. The preparation method of the coated titanium alloy according to claim 1, characterized in that, In step (1), the pretreatment process is ultrasonic cleaning for 8 - 12 min.
4. The preparation method of the coated titanium alloy according to claim 1, characterized in that, In step (2), the coating is made of AlMgScZr powder, and the mass ratio of Al:Mg:Sc:Zr in the powder is 93 - 95:4 - 6:0.4 - 1:0.1 - 0.
4.
5. The preparation method of the coated titanium alloy according to claim 1, characterized in that, In step (2), the particle size of the AlMgScZr powder is 15 - 40 μm.
6. The preparation method of the coated titanium alloy according to claim 1, characterized in that, In step (2), the selective laser melting parameters are: laser power is 370 W, scanning speed is 1000 mm / s, powder layer thickness is 0.03 mm, scanning spacing is 0.01 mm, spot diameter is 0.1 mm.
7. A coated titanium alloy, characterized in that, It is obtained by using the method according to any one of claims 1 - 6.